3 - Politics of Indexation: Beyond the Fingering & Figuring of Knowledge - Imtiaz Ahmed, (Africa Media Review, 2006)
The present essay traces the history of indexation, and discusses the challenge for indexing Africa in the 21st century. It then examines the possibilities and promises of indexing newer sources of knowledge drawing from the experiences of Afro-Asian relations through the journal, Identity, Culture and Politics: An Afro-Asian Dialogue.